The linkages between stomatal physiological traits and rapid expansion of exotic mangrove species (Laguncularia racemosa) in new territories - Bai, Jiankun; Meng, Yuchen; Gou, Ruikun; Dai, Zheng; Zhu, Xiaoshan; Lin, Guanghui (Frontiers in Marine Science, 2023)
The fast-growing exotic mangrove species (Laguncularia racemosa) has been widely introduced in new territories such as China to restore mangrove ecosystems. However, the invasiveness, as well as the mechanisms for the rapid expansion after the introduction are still not well studied. Here, we try to reveal possible micro-mechanisms for the fast expansion of L. racemosa, using the data on leaf stomata straits, gas-exchange parameters, stable isotope ratios, carbon-nitrogen allocation from L. racemosa and the adjacent native mangroves (Avicennia marina, Aegiceras corniculatum, Bruguiera gymnorhiza, Kandelia obovata) in Hainan Island, China. We found that the higher density but smaller size stoma of L. racemosa enhanced stomatal conductance and shorten the diffusion path of carbon dioxide, thereby increasing the photosynthetic rate. Moreover, the higher stomatal density of L. racemosa exerts a significant positive effect on transpiration, which thus accelerated the water transport and nutrient uptake to meet the advanced need for nutrients and water for fast-growing. The evidence from leaf δ13C and carbon-nitrogen allocation further proved that L. racemosa has a lower intrinsic water use efficiency but a higher rate of photosynthesis than native mangrove species. Our results suggest that stomatal morphological and physiological traits could strongly influence the growth of L. racemosa compared to the adjacent native mangroves, which provides a new perspective for the fast expansion of exotic mangrove species in China. These findings also suggest that L. racemosa has an invasive potential in native mangrove habitats, thereby the mangrove reforestation projects by introducing L. racemosa should be treated with caution.